2020
DOI: 10.3390/biom10081121
|View full text |Cite
|
Sign up to set email alerts
|

Glycine in Water Favors the Polyproline II State

Abstract: Conformational preferences of amino acid residues in water are determined by the backbone and side-chain properties. Alanine is known for its high polyproline II (pPII) propensity. The question of relative contributions of the backbone and side chain to the conformational preferences of alanine and other amino acid residues in water is not fully resolved. Because glycine lacks a heavy-atom side chain, glycine-based peptides can be used to examine to which extent the backbone properties affect the conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(75 citation statements)
references
References 93 publications
7
68
0
Order By: Relevance
“…28 The results revealed that pPII is driven by the tendency of water to maximize the number of hydrogen bonds between water and the functional groups of the central glycine, demonstrating that high pPII preference of amino acid residues stems from the water-backbone interactions. 28 Interestingly, Amber ff14SB was outperformed by the other two force fields with respect to its capacity to capture conformational dynamics of glycine residue in water. 28 Several recent studies revealed that CHARMM36m combined with its specialized TIP3P water model performs better than the other additive force fields, although there is still room for improvement.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…28 The results revealed that pPII is driven by the tendency of water to maximize the number of hydrogen bonds between water and the functional groups of the central glycine, demonstrating that high pPII preference of amino acid residues stems from the water-backbone interactions. 28 Interestingly, Amber ff14SB was outperformed by the other two force fields with respect to its capacity to capture conformational dynamics of glycine residue in water. 28 Several recent studies revealed that CHARMM36m combined with its specialized TIP3P water model performs better than the other additive force fields, although there is still room for improvement.…”
Section: Introductionmentioning
confidence: 92%
“…26 A follow-up study, Andrews et al asked whether alanine's preference for the pPII state stems from the backbone or alanine's side chain characteristics. 28 To this end, the experiment-based Gaussian modeling was applied to the central glycine residue in cationic GGG as a model of a peptide backbone, followed by the corresponding assessment of Amber ff14SB (with TIP3P), OPLS-AA/M (with TIP4P), and CHARMM36m (with the respective TIP3P model). 28 The results revealed that pPII is driven by the tendency of water to maximize the number of hydrogen bonds between water and the functional groups of the central glycine, demonstrating that high pPII preference of amino acid residues stems from the water-backbone interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stoichiometric amounts of Clatoms are added to ensure electroneutrality. Each 500 ns long trajectory is acquired using the velocity rescale thermostat 25 and the Berendsen barostat. 26 In order to assess the MD-based Ramachandran distributions we calculated the occupation of mesostates that cover populated regions of the Ramachandran plot.…”
Section: Simulations and Mesostate Calculationsmentioning
confidence: 99%
“…Backbone and side chain interactions with the solvent cause the intrinsic conformational propensities of amino acids to differ significantly. [23][24][25][26] Residues preferably sample the upper left quadrant of the Ramachandran plot (between 70 and 80%). [27][28][29][30][31] The remaining 20-30% are generally distributed over several turn-like conformations.…”
Section: Introductionmentioning
confidence: 99%